2019
DOI: 10.1177/1367549419886020
|View full text |Cite
|
Sign up to set email alerts
|

Inequality talk: How discourses by senior men reinforce exclusions from creative occupations

Abstract: Cultural Studies has drawn attention to the way that cultural and creative industries are marked by significant inequalities. This article explores how these inequalities are maintained, through fieldwork with senior men making decisions in cultural and creative industries. Drawing on 32 interviews with senior men across a range of cultural and creative industry occupations, conducted as part of a larger (N = 237) project, the analysis shows that misrecognition and outright rejection of inequalities are now no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…Yet despite the significant advantages enjoyed by those from middle-class backgrounds, there is strong evidence that such individuals tend to downplay (Sherman, 2017), misrecognise (Khan, 2011) or elide (Brook et al, 2019) such privilege. Indeed, it is these individuals who tend to believe most strongly that ‘hard work’ is the key determinant of career success (Mijs, 2019) and are least likely to acknowledge the role of coming from a privileged background (Hecht et al, 2020: 16–19).…”
Section: Meritocracy Class Identity and British Exceptionalismmentioning
confidence: 99%
“…Yet despite the significant advantages enjoyed by those from middle-class backgrounds, there is strong evidence that such individuals tend to downplay (Sherman, 2017), misrecognise (Khan, 2011) or elide (Brook et al, 2019) such privilege. Indeed, it is these individuals who tend to believe most strongly that ‘hard work’ is the key determinant of career success (Mijs, 2019) and are least likely to acknowledge the role of coming from a privileged background (Hecht et al, 2020: 16–19).…”
Section: Meritocracy Class Identity and British Exceptionalismmentioning
confidence: 99%
“…However, the simultaneous deployment of more self-serving valuations (aesthetic, and especially reputational and economic) suggests that certain people are less able to control the circulation of valuations, which has consequences for the extent to which they can feel authentically included in organizational contexts (Sayer 2000). More cynically, the circulation of moral valuations of marquee quotas may in some instances align more closely to the idea of "inequality talk," where the rhetorical commitment to diversity replaces more impactful interventions of inter-organizational change and may operate as a means for upholding pre-existing exclusionary boundaries (Brook et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, there has been a lack of research on the valuation and commodification of race and ethnicity in cultural production, (Hesmondhalgh and Saha 2013;Saha 2018), and inequality in creative industries more broadly (Brook et al 2021). However, this has changed in recent years, with some attention being paid to diversity initiatives.…”
Section: A Racism and Diversity Initiatives In Creative Industriesmentioning
confidence: 99%
“…In this way, little differs between performing artists (our focus) and wider society in the pre-existing inequalities, the uneven impacts of COVID-19 and government inattention in recovery planning. However, pre-COVID-19 research shows us that cultural work demonstrated deeper levels of inequality than other types of work (Brook et al, 2019; Hofman, 2015; Morcom, 2013; Saha, 2018; Tarassi, 2018), and radical change is needed to avoid the reinforcement of such injustice (see also Comunian and England, 2020).…”
Section: Artistic Precarity Within Cultural Ecologiesmentioning
confidence: 99%